Wettability-gradient surface fabricated by combining electrochemical etching and lithography. Issue 7 (3rd July 2017) - Zheng, Huanxi; Huang, Shuai; Liu, Jiyu; Chen, Faze; Yang, Xiaolong; Xu, Wenji; Liu, Xin
ABSTRACT: This paper proposes a simple, precise, and controllable method to fabricate wettability-gradient surfaces. Combining electrochemical etching and lithography, different micro/nanostructures can be obtained by adjusting the etching time. After being modified by low energy substances, low adhesive superhydrophobic and sticky hydrophobic regions can be obtained on one surface. Based on the obtained adhesion gradient, droplets of different volumes can be controlled to roll off at dissimilar tilted angles via designing sticky hydrophobic tracks with different widths. Directional transportation of water droplets on curve tracks is also realized based on the anisotropic sliding angles parallel and perpendicular to the tracks. GRAPHICAL ABSTRACT: